2022
DOI: 10.1177/03635465221077101
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Enhances Achilles Tendon Healing in an Animal Injury Model, and the Effects Are Dependent on Dose, Administration Time, and Mechanical Loading Stimulation

Abstract: Background: Corticosteroid treatments such as dexamethasone are commonly used to treat tendinopathy but with mixed outcomes. Although this treatment can cause tendon rupture, it can also stimulate the tendon to heal. However, the mechanisms behind corticosteroid treatment during tendon healing are yet to be understood. Purpose: To comprehend when and how dexamethasone treatment can ameliorate injured tendons by using a rat model of Achilles tendon healing. Study Design: Controlled laboratory study. Methods: An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…Previous studies investigating the tendon healing biomechanically found better results in early period only. 22,23 When these results were taken into consideration, the fact that no statistically significant difference was determined in the current study was thought to be due to the test having been performed in the 4th week. However, there are also studies in literature that have shown biomechanical healing with a test performed in the 4th week.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies investigating the tendon healing biomechanically found better results in early period only. 22,23 When these results were taken into consideration, the fact that no statistically significant difference was determined in the current study was thought to be due to the test having been performed in the 4th week. However, there are also studies in literature that have shown biomechanical healing with a test performed in the 4th week.…”
Section: Discussionmentioning
confidence: 81%
“…In a recent clinical trial, local injections of steroids (maximum three times at 4-week intervals) combined with exercise showed better outcomes in the treatment of tendinopathy than with placebo injections and exercise at 6 months ( Johannsen et al, 2022 ). In the rat tendon injury model, tendon healing was enhanced, and their mechanical properties improved when dexamethasone was administered for 5 days ( Dietrich-Zagonel et al, 2022 ). In our analysis of fluoroquinolone-induced and age-related tendinopathy from the IBM MarketScan data, the median administration period of dexamethasone was 12 and 10 days in the fluoroquinolone and older adult cohort, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated an immediate response of tendon cell activity and matrix protein expression. 11,13,18,26,44 Therefore, it is very likely that a matrix-synthesizing process is begun right after a rupture and that this will lead to a rise in collagen synthesis. The present study showed that a marked rise in collagen synthesis did not seem to be an immediate phenomenon within the first 2 weeks after an ATR in patients.…”
Section: Discussionmentioning
confidence: 99%